Crystal Growth, Structure, and Thermal Analysis of K₂Cu(SO₄)₂·6H₂O Tutton Salt (Thamar University Journal of Natural & Applied Sciences, 2024)
By using aqueous solutions of K2SO4 and CuSO4.5H2O with equal molecular ratios (1:1) light blue single crystals of K2Cu(SO4)2.6H2O (KCUSH) were prepared and grown by the slow evaporation technique of supersaturated aqueous solution at 309 K. X-ray diffraction measurements revealed the monoclinic structure, space group P21/a and Z = 2 for KCUSH crystal which is the structure of all Tutton salts family. The DTA and TGA measurements revealed that the evolution of the six water molecules of KCUSH takes place in two steps (two after four) at 351 K and 426 K respectively. It was found also that the two exothermic peaks at the end of DTA thermogram (792 K and 822 K) related to the material of the crucible (aluminum) in addition to the existence of Cu in our material KCUSH. By using platinum crucible, the two exothermic peaks disappeared and instead there is an endothermic peak at 796 K which refers to the melting process.